Hematological Status In Healthy And Discarded Bulls - Prasad, Anil; Kundu, A. K.; Mahapatra , A.P.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A study was undertaken on hematological status in healthy and discarded bulls. Hb level, TEC in discarded bulls were found to be less as compared to healthy bulls, whereas TLC was found to be significantely higher in discarded bulls. Eosinophilia may be one of the factor responsible for producing poor quality of semen in discarded bulls.
Keywords: Discarded bulls; Hematology; semen quality